Big dumb eyes : stories from a simpler mind - Bargatze, Nate (Grand Central, 2025)
"Nate Bargatze used to be a genius. That is, until the summer after seventh grade when he slipped, fell off a cliff, hit his head on a rock, and "my brain got, like, dented or something." Before this accident, he dreamed of being "an electric engineer, or a brain doctor, or maybe a math person who does like, math things for a living." Afterwards, a voice in his head told him, "It's okay. You're dumb now. All you got is standup."* But the "math things" industry's loss is our gain because Nate went on to become one of today's top-grossing comedians who breaks both attendance and streaming records. In hishighly anticipated first book, Nate talks about life as a non-genius. From stories about his first car (named Old Blue, a clunky Mazda with a tennis ball for a stick shift), life as a Southerner (Northerners constantly ask him things like, do you believe in dinosaurs?), and his first apartment where a rat chewed a hole right through the wall to how his wife keeps him in line and so much more. He also reflects on such topics as Vandy football and the origins of sushi (howcan a Philadelphia roll be from old-time Japan?). Nate's book is full of heart and it will make readers laugh out loud and nod in recognition, but it probably won't make them think too much. *Nate's family disputes this entire story"--